Den samskabende kirke? - Viftrup, Lars Buch (Dansk teologisk tidsskrift, 2020)
Co-production has become an important notion within public governance, particularly in municipalities. The Danish Folk Church has a long history of working together with the municipalities and is an institution with many civil resources. Through an empirical study involving the municipality, the church and citizens of Aarhus, this article discusses the implications of co-production for the church and its theology. St. Augustine’s concepts of the “City of God”, Luther’s concept of the “priesthood of all believers” and “vocation” and Luhmann’s concept of faith as dealing with “paradox” offer an analytical frame for understanding how the church co-produces the city. The “priesthood of all believers” underlines the “bottom up” character of the congregation and thereby its civil character, while the “City of God” as an ambivalent and paradoxical term for salvation holds together the tensions involved in co-production.